2021
DOI: 10.1097/aco.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

Discharging select patients without an escort after ambulatory anesthesia: identifying return to baseline function

Abstract: Purpose of reviewThe current standard of care requires ambulatory surgical patients to have an escort for discharge. Recent studies have started to challenge this dogma. Modern ultrashort acting anesthetics have minimal psychomotor effects after a couple of hours. Driving simulator performance and psychomotor testing return to baseline as soon as 1 h following propofol sedation. Recent findingsTwo recent reports of actual experience with thousands of patients found no increase in complications in patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Escort and availability of subject to have support at home are without doubt of importance for safety. A recent review addressed the importance to consider impaired both motor and cognitive capacity, thus supporting escort [4 ▪▪ ]. An accelerometer was used in a study for assessing motor function recovery, it showed that full motor functionality returns slowly and not complete during 1 week after surgery [5 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Escort and availability of subject to have support at home are without doubt of importance for safety. A recent review addressed the importance to consider impaired both motor and cognitive capacity, thus supporting escort [4 ▪▪ ]. An accelerometer was used in a study for assessing motor function recovery, it showed that full motor functionality returns slowly and not complete during 1 week after surgery [5 ▪ ].…”
Section: Introductionmentioning
confidence: 99%